Taking computer science to the underprivileged sectors of society - Díaz, Francisco Javier; Banchoff Tzancoff, Claudia Mariana; Harari, Ivana; Harari, Viviana (2009)
From the beginning, the National University of La Plata (UNLP)[1] has had a strong commitment with the com- munity, stressing and encouraging various extension activities. The Computer Science School [2] of the UNLP was cre- ated in the year 1999 and, ever since then, has participated in many activities to teach computer science to the least priv- ileged sectors of our society. We worked with senior citizens, representatives of social NGOs, teachers and professors of different levels, Technological Community Centers representatives, etc. This year, the School began working on a project called "Reducing the digital divide in children and adolescents". This project, framed in the University Volunteering Program of the National Ministry of Education [3], has the goal of taking technology to children and adolescents of low economic resources which attend social diners, and to their families. This project is an undertaking of great social impact, as it constitutes yet another manifestation among those encour- aged by the University and the Faculty with the goal of alleviating the digital divide existing between the who have ac- cess to technology and those who do not, by making ICTs (Information &Communication Technologies) approachable for everyone.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on e-Society ( 2009 feb. 25-28 : Barcelona)
Keywords: EDUCACIÓN EN INFORMÁTICA; TECNOLOGÍAS DE LA INFORMACIÓN Y DE LA COMUNICACIÓN (TICS); COMPUTADORAS Y SOCIEDAD